Osmanlı Devleti’nde Ermeniler : (1789-1850) - Külekçi, Cahit (My University, 2003)
Osmanlı Devleti'nde azınlık olarak yaşayan Ermenilerin durumu, tezde hem Ermeni hem de Osmanlı kaynakları taranarak karşılıklı olarak araştırılmış ve Ermeni Sorununun nedenleri ortaya konulmaya çalışılmıştır. 18. yüzyılın sonu, 19. yüzyılın başında Osmanlı Devleti ile Ermenilerin durumu, mümkün olduğu kadar objektif bir bakışla ele alınmıştır. Tezde de sık sık vurgulandığı üzere, henüz bu yıllarda iki millet arasında her hangi bir sorunun olmadığı gözlemlenmiştir. Ancak 1877- 1878 Osmanlı- Rus Savaşı ile bu durumun bozulduğu da bir sonuç olarak ortaya konmuştur. Tezde ise bu sonuç, Fransız İhtilali, Tanzimat Fermanı ve özellikle Yabancı Devletlerin Ermenileri kullanma çabalarına bağlanmıştır. The need for objective studies dealing with the controversial history of the Armenian minority in Ottoman Empire has led to the publication of this thesis documents compiled from the Ottoman sources and Armenian sources as well as possible. At the end of XVII. century and the beginning of the XIX. century, relations among the Armenian and Ottoman are very well. But at the end of Russo-Ottoman War of 1877-78 the name of the Ottoman Armenians appeared, for the first time, in international treaties and politics. In this thesis, we have objected to description the sources of the Armenian Question. And we have descripted the Revulation of France and Tanzimat for putting forward this question. Then we have concluded that, until 1850, there is not a proplem in the Ottoman Empire about Armenians.
Keywords: Osmanlı İmparatorluğu_Azınlıklar